THE IMPORTANCE OF THE USE OF SCALES OF DEVELOPMENT IN THE FOLLOW-UP OF PREMATURE HIGH RISK (Fiep Bulletin - online, 2011)
The premature baby presents a real risk in developing its growth due to a process that was interrupted abruptly without the same morphology was prepared for the birth. The use of test development as a selective tool promotes early intervention for deviations from normal growth and development in children, besides helping in the diagnosis and prognosis. The aim of this study was to measure the motor performance in preterm infants by measurement of specific instruments. The study was conducted in a University Hospital of Paraná, with ten baby boys and girls, with gestational age of 32.8 weeks who attended UNIT Intensive Care - ICU for 48 hours. It was noted that the evaluations performed by the Test of Infant Motor Performance - TIMP and the Alberta Infant Motor Scale, AIMS, are equivalent, identifying similarly to the driving condition of baby at risk. But the scale of TIMP was more sensitive since it indicated the need for monitoring of normal motor development, while at AIMS, the baby would be discharged early physiotherapy. The choice will depend on the scale of each population and objectives to be achieved by the professional. It is extremely important to monitor the child for professional physical therapy, to minimize the negative effects that prematurity can bring, because the earlier the diagnosis and intervention, the smaller the impact of these problems in a child's life. This study met our objective since it shows the importance of using specific tests to assess the DNPM in premature babies.
Keywords: Performance evaluation; child development; premature